Availability and use of CDROM products in Nigerian libraries and information centers - Adeniran, O.R.; Adigun, T.A.; Okoh, M.I.; Eyitayo, O.T. (Emerald Publishing Limited, 1994)
A study was conducted to find out the types of CD products in Nigerian libraries and information centres, and the uses to which they are being put. The study also tried to find out the sources of funding of such products, information about users, hardware configuration, and training facilities available in the country. Of the 157 questionnaires sent out, 85 usable returns (a 54% response rate) were received. The analysis revealed that 44 libraries had at least one PC with only nine of such centres having at least one CDROM workstation. There are 62 copies of 43 CD titles in Nigeria. Information on the discs is classified as bibliographic, full text, statistical, or general information. The subjects they cover in descending numeric order are agriculture, general reference, medicine, science and technology, social sciences, and education. Areas of applications include information retrieval, bibliographic compilations, current awareness services, library acquisition work, and downloading and uploading to local online databases. In general, CD use was minimal in most libraries as opposed to information centres where CD applications were well used by patrons, especially where the mass media was employed to advertise them. Most libraries funded their CD projects with their local budgets. The most frequently used computers are IBM or compatibles. Recommendations are also outlined.